First body book - Gifford, Clive; Jevons, Chris; Wood, Steven (Essex, England Miles Kelly Publishing, 2018)
Set off on a head-to-toe adventure through the human body with the help of appealing, contemporary artwork. Each spread explores a different body system through simple text and large, colourful anatomical illustrations. Also included is a wall poster showing all the body systems together
The world around us (human body)
1
Keywords: Generative organs -- Juvenile literature; Human anatomy -- Juvenile literature; Human physiology -- Juvenile literature